Design and Development of Tajweed Science Learning System Model Based on Android: Rancang Bangun Pemodelan Sistem Pembelajaran Ilmu Tajwid Berbasis Android - ricki ardiansyah; M. Arief Kurniawan; Maha Rani (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
This research was conducted to design a modeling that is used to build an Android-based Tajweed science learning system. The method used in the development of the Android-based Tajweed science learning system is the waterfall method. The learning system that was built adopted several components of LTSA. The system that was built focuses on the achievement of learning materials Tajweed science as part of the overall learning process. To design the system modeling in this study, UML was used. After the system design is complete, the design is implemented into Java coding which will later be exported into an apk that can be installed on an Android device. the results show that the system can run well on Android version 5.0, all features in the system can run well and in accordance with the design of the system designed with UML. Learning of Tajweed knowledge based on Android makes it easier to learn because it can overcome the learning of Tajweed science which is physically not possible and overcome the limitations of time, place and access. UML modeling is very suitable to be used in design to design a system model used in the application of the study of recitation.